Pola Asuh Orang Tua Single Parent dalam Mendukung Pendidikan Formal Anak di MTsS Al-Abror Muarasoma Kecamatan Batang Natal Kabupaten Mandailing Natal - Nur Hapni Nasution; Muhammad Darwis Dasopang; Sholeh Fikri (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2020)
The purpose of this study is to describe the parenting style of single parent parents in supporting children's education at MTsS al-Abror Muarasoma, Batang Natal District, Mandailing Natal Regency. The results showed that the type of democratic parenting performed by single parents was more dominant in supporting children's formal education. Meanwhile, authoritarian and permissive parenting styles still support children's education, but they are lower than democratic parenting. In democratic parenting, parents always control the development of their children, especially in terms of education. Parents always give their best for the development of their children's education both material issues such as school supplies, pocket money and others, as well as in material such as motivation, encouragement and praise. In authoritarian parenting, the attitude of parents is very strict towards their children, especially in terms of their education and if the children violate the rules that have been made such as laziness to learn, playfulness and decreased reports, the parents give their children punishment so that the children -the children prioritize their education. In Primitive parenting, parents act permissively. Children are always given freedom in their children's lives, including in their education.Key Words: parenting style of single parent; formal education; children